Perceived Training Needs of Farmers about Dairy Farming in Karnataka : A Perspective of Farmers and Veterinarians (Indian Journal of Extension Education, 2013)
An ex-post-facto and exploratory study was conducted to assess the training needs of dairy farmers as perceived by them and field veterinarians with a sample size of 120 dairy farmers and 66 field veterinarians in Davangere district of Karnataka state. The training needs of dairy farmers in major six areas viz. breeding, feeding, health care, housing and management, marketing & finance and dairy products preparation of dairy farming were assessed from the perspective of farmers and veterinarians. In major areas of dairy farming, farmers perceived higher training needs in health care followed by feeding and breeding while veterinarians perceived feeding as ’most important’ area followed by health care and breeding. Independent ’t’ test values indicate that veterinarians perceived higher extent of training needs for farmers in dairy products preparation, feeding and health care. The study concluded that farmers and veterinarians perceived higher extent of training needs in health care, feeding and breeding. Hence, the public and private extension agencies have to plan effective extension strategy based on the perceived training needs of the farmers for improving the livestock productivity.